Potential new alternative annual pasture legumes for Australian Mediterranean farming system - Loi A.; Nutt B.J.; McRobb R.; Ewing M.A. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
The southern Australian Mediterranean agricultural systems depend heavily on annual pasture legumes grown in rotation with cereals. Subterranean clover and annual medics have been the dominant species, however their performances have not always been reliable because of the great variation in soil, climatic characteristics and new intensive cropping regimes. In this paper we discuss some of the agronomic traits of new alternative pasture legumes with potential for the southern Australian systems.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)